2013
DOI: 10.1186/1746-6148-9-46
|View full text |Cite
|
Sign up to set email alerts
|

The spatial ecology of free-ranging domestic pigs (Sus scrofa) in western Kenya

Abstract: BackgroundIn many parts of the developing world, pigs are kept under low-input systems where they roam freely to scavenge food. These systems allow poor farmers the opportunity to enter into livestock keeping without large capital investments. This, combined with a growing demand for pork, especially in urban areas, has led to an increase in the number of small-holder farmers keeping free range pigs as a commercial enterprise. Despite the benefits which pig production can bring to a household, keeping pigs und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 48 publications
7
64
0
1
Order By: Relevance
“…However, for resource-poor farmers, the traditional pig production system is attractive (Verhulst 1993; Phiri et al 2003) because it requires much less space (Delgado et al 2001) and little to no housing due to the pig’s natural scavenging behavior to utilize kitchen leftovers and agricultural waste (Lekule and Kyvsgaard 2003). On the other hand, this scavenging behavior exposes them to diseases such as African swine fever or zoonotic agents such as Taenia solium , which have been reported from Uganda (Phiri et al 2003; Thomas et al 2013; Atuhaire et al 2014; Kungu et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…However, for resource-poor farmers, the traditional pig production system is attractive (Verhulst 1993; Phiri et al 2003) because it requires much less space (Delgado et al 2001) and little to no housing due to the pig’s natural scavenging behavior to utilize kitchen leftovers and agricultural waste (Lekule and Kyvsgaard 2003). On the other hand, this scavenging behavior exposes them to diseases such as African swine fever or zoonotic agents such as Taenia solium , which have been reported from Uganda (Phiri et al 2003; Thomas et al 2013; Atuhaire et al 2014; Kungu et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Similar lack of spatial correlation was reported by Morales et al (2008) in Mexico and explained by the combination of roaming behavior of pigs that covered large distances (2-5 km) daily (Copado et al, 2004) and mobile patterns of human in the study area. A study conducted in Kenya, geographically closer to our study area, found that free ranging pigs traveled an average of 4,340 m in a 12 h period and spent on average 47% of their time outside their homestead of origin and on average only 1.3% of their time interacting with the latrine area in their homestead of origin (Thomas et al, 2013). In such situation, ingestion of infective T. solium eggs by a free-roaming pig could therefore occur anywhere far from the homestead of origin and in the immediate circle of any tapeworm carrier.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, domestic pigs are often left to roam free in Uganda (Ouma et al., ), so their habit range can extend beyond smallholder farm perimeters where they encroach on various habitats. Collared free‐ranging domestic pigs in western Kenya travelled an average of 4340 m in a 12 h period and had a mean home range of 10 343 m 2 (Thomas et al., ). In this study, free‐ranging domestic pigs travelled large distances, throughout the day and night, with almost half of the time spent outside their homestead, extending the geographic range and habitats these pigs scavenge and travel in.…”
Section: Resultsmentioning
confidence: 99%